2018
DOI: 10.20892/j.issn.2095-3941.2017.0150
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of long non-coding RNA LCPAT1 inhibits autophagy in lung cancer

Abstract: Objective:Long non-coding RNAs (lncRNAs) are involved in numerous biological processes in lung cancer cells. In our previous studies, we identified a lncRNA, ENST00000439577, which is highly expressed in lung carcinomas, and termed it lung cancer progression-associated transcript 1 (LCPAT1). To characterize the role of LCPAT1 in lung cancer, we conducted the current study. Methods:Expression of LCPAT1 and autophagy-associated markers in tumor tissues and lung cancer cell lines was determined by real-time quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“… 26 LCPAT1 has been reported to promote lung cancer cell proliferation, and it participates in DNA damage. 17 , 27 To our knowledge, whether LCPAT1 is involved in BC regulation remains totally unclear. Our study reveals that LCPAT1 is upregulated in BC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 LCPAT1 has been reported to promote lung cancer cell proliferation, and it participates in DNA damage. 17 , 27 To our knowledge, whether LCPAT1 is involved in BC regulation remains totally unclear. Our study reveals that LCPAT1 is upregulated in BC cells.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that LCPAT1 regulates lung cancer. 17 However, other roles of LCPAT1 have not been explored. We found that LCPAT1 was highly expressed in BC tissues and correlated with poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…ATG12 is conjugated with ATG5 with the assistance of ATG7 to form the ATG5–ATG12 complex. LC3-I is finally transformed into LC3-II with the assistance of this complex, promoting autophagosome formation [ 27 29 ]. As mentioned above, autophagy plays different roles in tumors based on the type, stage, and genetic background of cancer [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with larger tumor size, advanced TNM stage, excessive growth and apoptosis process of HCC cells and tissues through sponging tumor suppressor miR-30b-5p and inducing autophagy (Liu et al, 2016). Yu et al (2018), recently noticed LCPAT1 lncRNA in LC which is directly regulated with autophagic flux. The overexpression of LCPAT1 and LC3 was found to be in both LC cells and tumor samples which accelerate the autophagic flux formation to promote carcinogenesis.…”
Section: Autophagy-inducing Lncrnas In Cancermentioning
confidence: 99%
“…The overexpression of LCPAT1 and LC3 was found to be in both LC cells and tumor samples which accelerate the autophagic flux formation to promote carcinogenesis. Whereas, knockdown of LCPAT1 can significantly reduce in vivo tumor size by reducing LC3, ATG3, ATG5, ATG7, ATG12, ATG14, and Beclin1expression (Yu et al, 2018). Chen and co-workers shown that PTENP1 is a lncRNA which is downregulated in HCC and SB based hybrid baculovirus vectors mediated insertion of PTENP1 potentially work as targeted anti-tumor agent in HCC cells by reducing proliferation and migration by activating autophagy in PI3K/AKT pathways (Chen et al, 2015).…”
Section: Autophagy-inducing Lncrnas In Cancermentioning
confidence: 99%